2022
DOI: 10.1038/s41467-022-33458-8
|View full text |Cite
|
Sign up to set email alerts
|

Fibrocytes boost tumor-supportive phenotypic switches in the lung cancer niche via the endothelin system

Abstract: Fibrocytes are bone marrow–derived monocytic cells implicated in wound healing. Here, we identify their role in lung cancer progression/ metastasis. Selective manipulation of fibrocytes in mouse lung tumor models documents the central role of fibrocytes in boosting niche features and enhancing metastasis. Importantly, lung cancer patients show increased number of circulating fibrocytes and marked fibrocyte accumulation in the cancer niche. Using double and triple co-culture systems with human lung cancer cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 60 publications
1
13
0
2
Order By: Relevance
“…In agreement with previous data [ 26 28 , 32 ], ET-1 induces HOFs to acquire features of CAFs, as an increase in platelet-derived growth factor receptor (PDGFR), fibroblast activated protein (FAP), and vimentin expression (Supplementary Fig. 1C ).…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…In agreement with previous data [ 26 28 , 32 ], ET-1 induces HOFs to acquire features of CAFs, as an increase in platelet-derived growth factor receptor (PDGFR), fibroblast activated protein (FAP), and vimentin expression (Supplementary Fig. 1C ).…”
Section: Resultssupporting
confidence: 92%
“…In an orthotopic model of breast cancer, the nanoparticles bearing the ET A/B R antagonist macitentan prevent fibrotic progression by regulating the CAF function [ 27 ]. Notably, ET-1-dependent fibrocyte-associated mechanisms promote lung tumor growth and metastasis, with local upregulation of ET-1 axis members, and bosentan interferes with all phenotypic switches that characterize the lung cancer-supportive niche [ 26 ]. In HG-SOC cells, ET-1 dictates the activation of a p53/YAP/HIF-1α transcriptional apparatus in fibroblasts, enhancing the release of VEGF circuits, regulating the DNA damage response, and the efficacy of PARPi treatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…По некоторым данным, при псориазе демиелинизирующая полиневропатия является результатом иммунологических механизмов воспаления, при котором окислительный стресс является этапом не только микроангиопатии в коже, но и процесса демиелинизации нервных волокон [38][39][40].…”
Section: рис 1 анализ динамики алтunclassified
“…При этом антагонизм к обоим типам рецепторов ЕТ-1 в значительной степени блокирует пролиферативное и промиграционное влияние фиброцитов на клетки рака легкого in vitro и in vivo, т.е. ингибирование рецепторов ЕТ-1 препятствует всем фенотипическим переключениям, которые характеризуют нишу, поддерживающую рак легкого, -усиленной пролиферации и миграции опухолевых клеток, дифференцировке моноцитов в макрофаги с преобладанием М2-типа, миграции эндотелиальных клеток и образованию трубок, ангиогенезу [38].…”
Section: вклад авторовunclassified
“…In human breast tissue, CD34 + cells have been detected in the extracellular matrix surrounding breast lobules and low grade DCIS but are no longer detected when SMA + myofibroblasts were increased surrounding high grade DCIS and invasive ductal carcinoma [23,24], which is suggestive of differentiating fibrocytes. While recent single cell RNA sequencing studies have identified fibrocytes in lung tumors [25,26], the role of fibrocytes in altering the tumor microenvironment in obesity has not been examined.…”
Section: Introductionmentioning
confidence: 99%